2001
DOI: 10.1046/j.0953-816x.2000.01436.x
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch between BDNF mRNA and protein expression in the developing visual cortex: the role of visual experience

Abstract: Brain-derived neurotrophic factor (BDNF) messenger RNA (mRNA) expression in the rat visual cortex of young and postnatal day 90 (P90) animals is developmentally regulated and influenced by visual experience. In the present paper we compared the expression of BDNF mRNA to the actual changes of BDNF protein occurring during postnatal development and verified whether BDNF protein distribution is controlled by visual activity. To achieve this aim we analysed BDNF mRNA and/or BDNF protein cellular distribution in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 50 publications
4
38
1
1
Order By: Relevance
“…This may raise the concern that BDNF rs6265 methylation represents something indirectly associated with schizophrenia, rather than a risk factor. However, since the expression of BDNF mRNA does not reflect the rate of protein synthesized, 42 the relationship of BDNF rs6265 methylation with BDNF protein level may also be the result of the contribution of other elements, such as the expression of non-coding transcripts, affecting the level of BDNF protein by acting at a post-transcriptional level. 43,44 Moreover, since human platelets represent a main source of serum BDNF protein but not of BDNF mRNA, serum BDNF has been postulated not to originate from megakaryocyte precursor cells, while potential sources include CNS 41,45,46 ; indeed, it has been shown that BDNF can readily cross the brain-blood barrier.…”
Section: Resultsmentioning
confidence: 99%
“…This may raise the concern that BDNF rs6265 methylation represents something indirectly associated with schizophrenia, rather than a risk factor. However, since the expression of BDNF mRNA does not reflect the rate of protein synthesized, 42 the relationship of BDNF rs6265 methylation with BDNF protein level may also be the result of the contribution of other elements, such as the expression of non-coding transcripts, affecting the level of BDNF protein by acting at a post-transcriptional level. 43,44 Moreover, since human platelets represent a main source of serum BDNF protein but not of BDNF mRNA, serum BDNF has been postulated not to originate from megakaryocyte precursor cells, while potential sources include CNS 41,45,46 ; indeed, it has been shown that BDNF can readily cross the brain-blood barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, YAC or BAC transgenic mouse lines were used to monitor mRNA expression (14 -16). However, it is very well known that the levels of the mRNA encoding BDNF do not correspond to the actual BDNF protein levels in vivo (43).…”
Section: Discussionmentioning
confidence: 99%
“…These activity-dependent signalling pathways induce neural gene transcription by modulating the function of transcriptional activators and repressors which finally lead to structural changes of the nerve cells (West and Grace, 2002). Accordingly, 2-4 h of light stimulation are sufficient to increase dendritic growth rates (Sin et al, 2002), or to enhance translation of the neurotrophic factor BDNF (Tropea et al, 2001) while blocking synaptic activity for 1 h enhances tectal cell death (Galliresta et al, 1993) and reduces growth of tectal dendrites or promotes arborisation of retinal ganglion cell axons (O'Rourke et al, 1994;Rajan et al, 1999;Cohen-Cory, 1999). Increased axonal arbor dynamics are also achieved within 2 h by tectal BDNF application (Cohen-Cory and Fraser, 1995; Alsina et al, 2001).…”
Section: Discussionmentioning
confidence: 99%